A Preliminary Study on Habitat Amelioration of Abandoned Maldhari Nesses in Gir National Park and Sanctuary - Pati, B. P.; Hanif, Belim M. (Indian Forester, 2006)
The present investigation is concerned with the regeneration status, habitat utilization and herbaceous biomass production status with respect to the relocated and present Maldhari nesses, which elucidate the impact of human beings (i.e. Maldharis) and their livestock on the Gir National Park and Sanctuary. In abandoned nesses of the Gir National Park, the average regeneration rate and the herbaceous biomass was more in comparison to the abandoned nesses of the Sanctuary. This was because the latter sites are located near the present nesses. In the present nesses, the regeneration rate and the herbaceous biomass was nil at 0m, minimum at 200m and slightly higher at 500m. In present nesses, non-palatable weight of herb biomass was the maximum at all distances and at all intervals and was the minimum or absent in the abandoned nesses. The average percentage utilization of habitat by wildlife at present nesses was very low in 200m (25%) and 500m (45%), whereas in abandoned nesses the average percentage of utilization of habitat by wildlife was 70% at 0m, 65% at 200m and the highest 85% at 500m.